Pengaruh Kualitas Produk, Kualitas Pelayanan, Strategi Pemasaran Syariah,Terhadap Kepuasan Konsumen Dan Kepercayaan Konsumen Pada UMKM Mohawi Konawe Kepulauan - Dharman Dharman (Journal of Management and Creative Business, 2024)
The purpose of this study is to analyze the impact of product quality, service quality, and Islamic aw marketing strategies on consumer satisfaction and consumer. The subjects of this investigation are MSME customers in Roko Roko Raya Village, Konawe Islands. The data collection technique was carried out using observation and questionnaire and analysis data used SEM. The research results show that: Product quality has a significant positive impact on Shariah marketing strategies. Service quality has a significant negative impact on Shariah marketing strategy. Product quality has a significant positive impact on consumer satisfaction. Service quality has a significant negative impact on consumer satisfaction. Shariah marketing strategies have a significant positive effect on consumer satisfaction. Product quality does not have a significant impact on consumer trust. Service quality has a significant positive impact on consumer trust. Shariah marketing strategies do not have a significant impact on consumer trust. Consumer satisfaction has a significant positive impact on consumer trust. Shariah marketing strategies can convey the impact of product quality on consumer satisfaction. Shariah marketing strategies can convey the impact of service quality on consumer satisfaction. Shariah marketing strategies can convey the impact of product quality on consumer trust. Shariah marketing strategies can convey the impact of service quality on consumer trust.